Mechanistic Details on the Conversion of Si–O to Si–C Bonds Using Metal Hydrides: A Density Functional Theory Study. Issue 10 (12th February 2019) - Butera, Valeria; Fukaya, Norihisa; Choi, Jun‐Chul; Sato, Kazuhiko; Choe, Yoong‐Kee
Abstract : We report results of density functional theory (DFT) calculations conducted to investigate the reaction mechanism for the formation of MeSi(OMe)3 from tetramethoxysilane [Si(OMe)4 ], using metal hydrides. In the present study, the effects of three different metal hydrides on the conversion reaction were investigated. This procedure represents an alternative route for the direct conversion from Si–O to Si–C bonds. Our DFT calculations revealed that the most energetically favorable reaction path that leads to the formation of the final product [MeSi(OMe)3 ] proceeding through the formation of HSi(OMe)3 as an intermediate. We found that the new Si–C bond originates from the methyl group transfer from another molecule of Si(OMe)4, and that this was the most energetically demanding process. We have also identified the origin of the reactivity difference between three metal hydrides. In agreement with the experiment, our results indicated that NaH was the best choice for this conversion reaction. Abstract : The reaction mechanism for the formation of MeSi(OMe)3 from tetramethoxysilane, Si(OMe)4, using metal hydrides, is investigated using DFT. The most energetically favorable path to the final product, MeSi(OMe)3, proceeds through intermediate HSi(OMe)3 . The new Si–C bond originates from the methyl group transfer from another molecule of Si(OMe)4, and this is the most energetically demanding process.